Purifying Proteins for Proteomics: A Laboratory Manual - Simpson (Richard J) Ed. ("S-25 Green Park Extn, Uphaar Linema Market,New Delhi - 110 016", 2004)
Proteins ; Proteomics
22.5
Keywords: Proteins ; Proteomics